Beginning Nokia Apps Development Qt and HTML5 for Symbian and MeeGo - Rischpater, Ray.; Zucker, Daniel; SpringerLink (Online service) (Berkeley, CA : Apress, 2010)
While media buzz regularly circulates around iPhone and Android, Nokia still leads the pack in terms of world market share. Symbian, for instance, remains the most widely used mobile operating system. With Nokia's open development platform, the opportunities available for mobile developers to target this vastly popular operating system are abundant and clear. Use Qt to target both platforms: Symbian, the most widely used mobile operating system in the world, as well as MeeGo, the Intel/Nokia platform for mobile devices. Develop HTML5 applications for both Symbian and MeeGo platforms that will run with little modification on other mobile platforms. Novice developers learn the basics of Qt with a mobile slant, giving them the ability to target both desktop and mobile platforms.
Design -- Introducing Nokia$1 (Bs Software Platform -- Designing Your Application -- Developing Your Application -- Working with the Nokia Qt SDK -- Beginning Qt Development -- Doing More with Qt -- Introducing Qt Quick -- Developing with HTML5 -- Distribute -- Testing Your Application -- Deploying Your Application.s
Keywords: Computer science; Computer Science; Computer Science, general